2006
DOI: 10.1007/s10549-005-9130-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Signification of Cytosolic Hyaluronan Levels in Invasive Breast Cancer

Abstract: Our results suggest that high intratumoral levels of HA may be associated with tumors of favorable evolution in certain subgroups of patients with breast cancer. Thus, HA may provide additional prognostic information to that given by other biochemical markers currently used in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
(52 reference statements)
1
8
1
Order By: Relevance
“…However, in the only published work analyzing levels of high molecular weight hyaluronan (HMW-HA) by immunoradiometric assays, we found a signiWcant and positive relationship between high intratumoral levels of hyaluronan and classic clinicopathological parameters indicative of lower tumor aggressiveness, such as a high histological grade of diVerentiation, diploid tumors and both estrogen (ER) and progesterone receptor (PR) positive tumors. Consistent with these Wndings, we also determined that high HMW-HA levels were signiWcantly associated with a longer relapse-free survival in the subgroup of patients with tumors of the ductal histological type, even among those with node-negative tumors, and also when we considered diVerent subgroups of patients with regard to the adjuvant systemic therapy received (Corte et al 2006).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in the only published work analyzing levels of high molecular weight hyaluronan (HMW-HA) by immunoradiometric assays, we found a signiWcant and positive relationship between high intratumoral levels of hyaluronan and classic clinicopathological parameters indicative of lower tumor aggressiveness, such as a high histological grade of diVerentiation, diploid tumors and both estrogen (ER) and progesterone receptor (PR) positive tumors. Consistent with these Wndings, we also determined that high HMW-HA levels were signiWcantly associated with a longer relapse-free survival in the subgroup of patients with tumors of the ductal histological type, even among those with node-negative tumors, and also when we considered diVerent subgroups of patients with regard to the adjuvant systemic therapy received (Corte et al 2006).…”
Section: Introductionsupporting
confidence: 81%
“…Histochemical studies have reported the expression of hyaluronan as being associated with poor prognosis in some groups of patients with breast carcinomas (Auvinen et al 2000;Bertrand et al 1992), whereas high hyaluronan levels determined by immunoradiometric assays have been associated with high ER or PR content, as well as a favorable outcome in patients with ductal invasive breast cancer (Corte et al 2006). Similarly, Kosunen et al found that a reduced expression of hyaluronan was a strong indicator of poor survival of patients with squamous cell carcinomas (Kosunen et al 2004), but this is a totally diVerent cancer type which shows a reduced hyaluronan expression in poorly diVerentiated advanced tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirm a previous studies evaluated HA content in malignant breast lesions and found that the stromal tissue in breast cancer contained more HA compared with normal breast or benign lesions. [17][18][19] The intensity of the stromal HA was reported to be significantly related to poor differentiation of the tumors, axillary lymph node positivity, and short overall survival of the patients. 20,21 Several major molecular characteristics of HA may contribute to its role in tumor cell behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have examined the influence various GAGs on breast cancer cell lines, including the regulation of FGF response to HS chains (Delehedde et al, 1996;Nurcombe et al, 2000), the ability of heparin and low molecular weight heparins to inhibit metastisis (Mellor et al, 2007), increases in motility on HA exposure (Herrera-Gayol and Jothy, 2001), and the inhibitory effect of lowering HS sulfation (Delehedde et al, 1996;Guo et al, 2007). Breast cancer cell lines were also found to secrete factors, which unregulated HA production in other cell lines (Corte et al, 2006). However, there been relatively few studies that investigate GAG changes in vivo in cancerous breast tissue.…”
mentioning
confidence: 99%